(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The authors looks at the common and specific features of the relations between the state and religion in the CIS countries. He offers his opinion on the religious situation in CIS and the other post-Soviet countries in the European part of the CIS , as well as in the Caucas describes how religion is used for statical purposes. This publication shows how the traditional religious values in CIS have played an important role in helping the re-emergence of their national identities, while in CIS the religious institutions have been adapting to that change in national identity. In the case of Ukraine the different branches of the church have been developing in different ways, responding to competing ideas of what it means to be Ukrainian. In all four states the churches are looking to entrench their role in society and are testing the limits of their influence given that they are the most trusted institutions in each country. The Russian Church and state have also been trying to promote this traditional values agenda as part of their ethos of ‘Р. Russian World’ with which they have been looking to influence the churches and societies of their ‘near abroad’. The publication has found that:In Ukraine the impact of the conflict has dramatically changed the balance of power between the two largest churches, the Ukrainian Orthodox Church-Moscow Patriarchate (UOC-MP) and the Ukrainian Orthodox Church-Kiev Patriarchate (UOC-KP).In CIS tradional religions is an independently powerful political actor that has played an important role in the socialpolitical landscape with national culture central to the rebuilding of national identity in the post-Soviet period. church. Key words: Secular, state, religion, religious renaissance, post-Soviet states, CIS countries, Local church in Ukraine, Caucasus, religious communities, religious situation, multiconfessionalism, multiculturalism, globalization.